OCCURRENCES OF TROPICAL ANGUILLIDS EELS IDENTIFIED THROUGH DNA BARCODES AT KEDURANG RIVER, SUMATRA ISLAND, INDONESIA - Anna-Lena Musch; Arif Wibowo; Rezki Antony; Samuel Samuel; Dwi Atminarso (Research Center for Fisheries, 2021)
Understanding the geographic distribution of tropical anguillids is important for the conservation of these species. Delimitation of species distribution area is a fundamental task with important implications for the understanding of biodiversity and conservation. However, their geographic ranges are poorly understood, mostly because of the technical difficulties of identifying anguillids by morphological characteristics, especially at the glass eel stage. The current work aims to provide the information on recruitment of tropical anguilid eels in the Kedurang River by using analysis of species identification of an informative DNA segment of Cytochrome Oxidase Sub unit1. Results showed that PCR, sequencing and analysis of an informative DNA can be a useful complement to morphological study for more complete biodiversity assessments. The anguillid eels found in Kedurang River were identiﬁed and further validated as A. bicolor bicolor, A. interioris, A. bengalensis bengalensis, and A. marmorata through glass and adult eels. This study suggests the occurrence of A. interioris in Estuary of Sumatera River would provide the first confirmation for this species in the territory. The information can be useful for understanding the geographic distribution this species for the establishment and allocation of risk categories to species, both in national protection lists and in those of treaties and international conventions.